The knowledge of pregnant teenagers on Speech Therapy related to maternal-infant health care - doi:10.5020/18061230.2007.p207 - Daniela Carvalho Neves; Aline Maria de Araújo Aguiar; Izabella Santos Nogueira de Andrade (Universidade de Fortaleza, 2012)
This study had as its objective to investigate the knowledge of pregnant teenagers on Speech Therapy related to maternal-infant health care. A qualitative analysis was made based on a thematic investigation of the subject matter. Ten pregnant teenagers with chronological age between ten and nineteen years old joined in the survey. They found themselves around the fifth and ninth months of gestation age, being attended at the Center of Pregnant TeenagersAttention Care at Fortaleza General Hospital. The collection of data involved the application of a semi-structured interview broaching topics that could identify what the pregnant teenagers knew about Speech Therapy and maternal-infant care. Education interventions, related to Speech Therapy health promotion, were also accomplished. The results pointed out that the pregnant teenagers' level of knowledge on aspects such as: food transition and utensils, oral habits, language stimulation and hearing loss detection, was still incipient and unsatisfactory. It is concluded that the knowledge of the pregnant teenagers on Speech Therapy related to maternal-infant health care was unsatisfactory, which demonstrates the importance of education interventions related to human communication health care for this studied sample.